2007
DOI: 10.1002/pmic.200600938
|View full text |Cite
|
Sign up to set email alerts
|

Suction blister fluid as potential body fluid for biomarker proteins

Abstract: Early diagnosis is important for effective disease management. Measurement of biomarkers present at the local level of the skin could be advantageous in facilitating the diagnostic process. The analysis of the proteome of suction blister fluid, representative for the interstitial fluid of the skin, is therefore a desirable first step in the search for potential biomarkers involved in biological pathways of particular diseases. Here, we describe a global analysis of the suction blister fluid proteome as potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 120 publications
7
97
1
Order By: Relevance
“…Some of the first studies were those of Celis and co-workers in breast carcinomas (80) and adipose tissue from breast carcinoma patients (81) using the tissue elution method, that has later also been used, e.g., in liver (443). A proteomics approach has also been applied on IF isolated by centrifugation in rat bone marrow (488), pig skin (68) and human ovarian carcinomas (184), by capillary ultrafiltration in fibrosarcomas in mice (204), a human head and neck squamous carcinoma (440) and by the suction blister technique in human skin (248). The available data suggest that this is an emerging area with significant potential.…”
Section: E Tissue-specific Proteins In Ifmentioning
confidence: 99%
“…Some of the first studies were those of Celis and co-workers in breast carcinomas (80) and adipose tissue from breast carcinoma patients (81) using the tissue elution method, that has later also been used, e.g., in liver (443). A proteomics approach has also been applied on IF isolated by centrifugation in rat bone marrow (488), pig skin (68) and human ovarian carcinomas (184), by capillary ultrafiltration in fibrosarcomas in mice (204), a human head and neck squamous carcinoma (440) and by the suction blister technique in human skin (248). The available data suggest that this is an emerging area with significant potential.…”
Section: E Tissue-specific Proteins In Ifmentioning
confidence: 99%
“…6 Quantitative PCR-based microRNA profiling was performed, and 175 miRs were detected with a C t -value <40 which was sufficient to be considered in the following analysis ( Figure S1 and Table S1). Setting a threshold of 1.…”
Section: Secretory Mir Levels During Skin Ageingmentioning
confidence: 99%
“…6 Several studies demonstrated the role of PAR-2 signalling in the process of pigmentation in various experimental conditions (S11-14). In addition, downregulated PAR-2 expression was reported in vitiligo lesional skin, which is associated with melanin loss in keratinocytes.…”
Section: -5mentioning
confidence: 99%
“…SmTOR might be essential at that specific time-point. Many complement proteins are produced by epidermal cells (Timar et al 2007) and several authors have shown that complement proteins diffuse from the vascular compartment to the dermis and epidermis (Kool et al 2007 ;Hansell et al 2008). The complete complement cascade is active in the skin as indicated by the role of complement in many human blistering skin diseases (Lessey et al 2008).…”
Section: Discussionmentioning
confidence: 99%